Coronary Bioresorbable Vascular Scaffold Use in the Treatment of Coronary Artery Disease. (July 2016) - Testa, Luca; Latib, Azeem; Montone, Rocco A.; Colombo, Antonio; Bedogni, Francesco
Abstract : Bioresorbable vascular scaffolds (BVS) represent a promising novel approach for the treatment of coronary artery disease. BVS promise to address some of the well-known limitations of current drug-eluting stents, while providing a transient scaffolding of the vessel to prevent acute vessel closure/recoil. Drug elution by BVS prevents neointimal proliferation in a similar fashion to drug-eluting stents, and complete bioresorption is associated with late vessel lumen enlargement, plaque regression, and restoration of vasomotion. Based on the pathophysiological reasons and on the results derived from clinical studies, BVS are increasingly being used in clinical practice. The aim of this review is to provide an overview of the current evidence supporting the use of BVS in clinical practice. In particular, we will discuss the randomized controlled trials and registries evaluating the clinical outcome of these devices, with a special focus on their application in patients with acute coronary syndrome and in specific lesion subsets (bifurcations, chronic total occlusions, and in-stent restenosis).